Prompting and visualising monitoring outcomes: Guiding self-regulatory processes with confidence judgments. (June 2017) - Schnaubert, Lenka; Bodemer, Daniel
Abstract: Sensible self-regulated study decisions are largely based on monitoring learning and using this information to control learning processes, but research has found that such processes may not be initiated automatically. To support learners, we adopted prompting and visualisation methods by asking learners to assign confidence ratings to learning tasks and visualising them during re-study, and tested the effects on metacognitive and cognitive measures in an experimental study ( N  = 95). Results show that prompting monitoring increased study efforts while visualising monitoring outcomes during learning focussed these efforts on uncertain answers. Due to low monitoring accuracy, metacognitively sensible regulation did not lead to cognitive learning gains. While the results support the idea of using visualisation techniques to implicitly guide self-regulated learning, more needs to be done to increase monitoring accuracy. Further, our study suggests that researchers should be aware of the effect that assessing confidence judgments has on subsequent learning behaviour. Highlights: Learners not always monitor their learning or use the information to guide learning. Support may be realised by prompting and visualisation techniques. Prompting monitoring affected the magnitude of study behaviour. Visualising monitoring ratings focused study efforts on uncertain material. Low monitoring accuracy impeded transfer to cognitive learning outcomes.